A Method for Trust Quantification in Cloud Computing Environments - Xiaohui Li; Jingsha He; Bin Zhao; Jing Fang; Yixuan Zhang; Hongxing Liang (International Journal of Distributed Sensor Networks)
Cloud computing and Internet of Things (IoT) are emerging technologies that have experienced rapid development in recent years. While cloud computing presents a new platform over which services are offered to the user more conveniently, IoT facilitates the collection of a large amount of data via interconnected wireless sensors for event monitoring and control. In such environments, ownership and control over the data may lead to potential conflict between the protection of data and the provision of services. Thus, cloud security has received a great deal of attention in recent years. In this paper, we propose a method for trust quantification based on fuzzy comprehensive evaluation theory for cloud computing to protect user data through trust quantification of cloud services after we introduce trust ontology for cloud services and define user preference trust values. By enhancing the existing trust concept based on dynamic requirements, we introduce some cloud service attributes to study layered service representation for trust preference and then apply the fuzzy comprehensive evaluation theory to perform trust quantification. We also perform some experiment to show that the proposed method is effective and can dynamically perform trust quantification to deal with malicious acts of nonfaithful services.